1927
DOI: 10.1001/archpedi.1927.04130210118014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Rickets Prior to 1650

Abstract: When Whistler published his slim Leyden graduate thesis on rickets in 1645, which was followed by Glisson's adequate volume in 1650, the origin of what was then called "an entirely new disease" was attributed to conditions having little relation to diet and sunshine. But, by the end of the eighteenth century, authorities were able to conclude that climate and especially dampness had much to do with the origin of rickets, and that improper food also had some part in its etiology.From the time of the first descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

1938
1938
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Indeed, a number of diseases, including rickets, were brilliantly known in ancient China. Iconography of the industrial cities of Germany and Holland, at least 200 years before Whistler’s description, definitely support the thesis that rickets existed to some extent at all times and periods of the world’s history [46,53,54]. …”
Section: Historical Notesmentioning
confidence: 75%
See 1 more Smart Citation
“…Indeed, a number of diseases, including rickets, were brilliantly known in ancient China. Iconography of the industrial cities of Germany and Holland, at least 200 years before Whistler’s description, definitely support the thesis that rickets existed to some extent at all times and periods of the world’s history [46,53,54]. …”
Section: Historical Notesmentioning
confidence: 75%
“…Children who were frail were often confined indoor with poor exposure to sunlight. Another remarkable pre-Whistler rickets case may have been represented in Caravaggio’s Amore dormiente [44,45,46]. …”
Section: Historical Notesmentioning
confidence: 99%
“…W hereas we are now very familiar with the condition we call rickets, that was not so in the early 17th century, when it seemed to be a new disease in England. It has been suggested that the condition had been described in early Chinese writings and in Roman times and that rickets was depicted (1) in paintings from the 15th century, but it is difficult to accept any of these suggestions with complete confidence. However, the original 17th century manuscripts and publications still exist in London libraries and they make it possible to review the position at that time.…”
Section: Introductionmentioning
confidence: 99%
“…Presumptive rickets has also been described from skeletons associated with Indian tribes in both North and South America. 1 In the 1870s, rickets was widespread in the United States; in Philadelphia, 25% of the children were described as rachitic. Between 1910 and 1961, rickets was cited as the cause of death of more than 13,000 children.…”
Section: Introductionmentioning
confidence: 99%